2018
DOI: 10.1186/s12916-018-1083-x
|View full text |Cite
|
Sign up to set email alerts
|

Avoidable waste of research related to outcome planning and reporting in clinical trials

Abstract: BackgroundInadequate planning, selective reporting, and incomplete reporting of outcomes in randomized controlled trials (RCTs) contribute to the problem of waste of research. We aimed to describe such a waste and to examine to what extent this waste could be avoided.MethodsThis research-on-research study was based on RCTs included in Cochrane reviews with a summary of findings (SoF) table. We considered the outcomes reported in the SoF tables as surrogates for important outcomes for patients and other decisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 50 publications
2
46
1
2
Order By: Relevance
“…Development of a core outcome set would result in more consistent reporting of outcomes and choice of outcome measures. Effectiveness comparisons and reduced outcome reporting selection bias would be facilitated …”
Section: Discussionmentioning
confidence: 99%
“…Development of a core outcome set would result in more consistent reporting of outcomes and choice of outcome measures. Effectiveness comparisons and reduced outcome reporting selection bias would be facilitated …”
Section: Discussionmentioning
confidence: 99%
“…Poor trials are not unique to wound care, as many examples exist of research waste caused by poor trials in other aspects of healthcare. [2][3][4] Trials can be improved in a variety of ways, such as by creating more appropriate reporting standards, 2,3,14 improving the methods applied, 1,3 or improving regulation. 15 However, the definition of what constitutes a good trial changes over time as new and innovative trial designs emerge.…”
Section: Improving Clinical Trialsmentioning
confidence: 99%
“…Trials in any aspect of healthcare can be improved through more efficient reporting, methods, or regulation. [1][2][3]14,15 However, the notion of improving the design and conduct of trials through a unifying community of practice such as WReN has not been previously reported. As such, exploring the benefits of a community of practice approach to improving wound trials and research (e.g., WReN) in other nations is worthwhile.…”
Section: The Wounds Research Networkmentioning
confidence: 99%
See 2 more Smart Citations